Controller Responsibility of the Insurance Company in the Event of Failure to Pay the Insurance Policy of PT Jiwasraya Insurance Company - Soca Daru Indraswari (PT FORMOSA CENDEKIA GLOBAL, 2023)
Law has the goal of producing orderly social rules, producing discipline, balance and justice. Mochtar Kusumaatdmaja said